2000
DOI: 10.1097/00126334-200005010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases and the Increased Risk for HIV Transmission: Implications for Cost-Effectiveness Analyses of Sexually Transmitted Disease Prevention Interventions

Abstract: We estimated the annual number and cost of new HIV infections in the United States attributable to other sexually transmitted diseases (STDs). We used a mathematical model of HIV transmission to estimate the probability that a given STD infection would facilitate HIV transmission from an HIV-infected person to his or her partner and to calculate the number of HIV infections due to these facilitative effects. In 1996, an estimated 5,052 new HIV cases were attributable to the four STDs considered here: chlamydia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 76 publications
0
63
1
1
Order By: Relevance
“…In 10 to 20 percent of women with gonococcal infection, pelvic inflammatory disease develops which includes a variety of inflammatory conditions of the upper reproductive tract including endometritis, parametritis, and salpingitis and often leads to chronic pelvic pain, infertility, and ectopic pregnancy (2). In addition, epidemiologic and clinical studies provide strong evidence that gonococcal infections facilitate the transmission of HIV-1 infection and that control of gonorrhea needs to remain high on the agenda of HIV-1 control programs (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In 10 to 20 percent of women with gonococcal infection, pelvic inflammatory disease develops which includes a variety of inflammatory conditions of the upper reproductive tract including endometritis, parametritis, and salpingitis and often leads to chronic pelvic pain, infertility, and ectopic pregnancy (2). In addition, epidemiologic and clinical studies provide strong evidence that gonococcal infections facilitate the transmission of HIV-1 infection and that control of gonorrhea needs to remain high on the agenda of HIV-1 control programs (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…1 Untreated STD is more prone to disease spread and runs a higher risk of contracting HIV; STDs increases the risk of HIV. 2 The diagnosis and subsequent treatment often depends on clinical and laboratory diagnosis. In vaginal discharge, clinical diagnosis is often inaccurate and has limited value.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic peptides including defensins are required for anti-HIV activity of vaginal fluid from healthy women (Venkataraman et al, 2005). While it is well established that sexual transmitted infections (STIs) significantly increase the likelihood of HIV transmission (Chesson and Pinkerton, 2000;Cohen et al, 1997;Galvin and Cohen, 2004;Mabey, 2000;Plummer, 1998) and that levels of defensins including HNPs, HBDs and HD5 in genital fluid, are elevated in patients with STIs (Porter et al, 2005;Simhan et al, 2007;Valore et al, www.intechopen.com 2006; Wiesenfeld et al, 2002), the role of defensins in HIV transmission seems to be complex. Studies using a cohort of HIV uninfected sex workers in Kenyan demonstrated the association between an increase in HNPs and LL-37 levels in the IgA-depleted cervicovaginal secretions from women with bacterial STIs and increase in HIV acquisition, despite that cervicovaginal secretions with high levels of HNPs and LL-37 exhibited anti-HIV activity in vitro (Levinson et al, 2009).…”
Section: Role Of Defensins In Hiv Pathogenesis and Transmissionmentioning
confidence: 99%